Peningkatan Kemampuan Bercerita melalui Media Rotasia pada Anak Didik Kelompok A1 TK Pamekar Budi Desa Candisari Kecamatan Mranggen Kabupaten Demak Semester 1 Tahun Pelajaran 2016/2017 - Istirokah Istirokah (JP3 (Jurnal Pendidikan dan Profesi Pendidik), 2017)
Age 4 - 6 years is the golden age in the development of child's life. At this age, all the potential ability of children can be developed optimally. One of the abilities that need to be developed is the child's ability to understand and express expressive language (basic competence 3-11-4.11) with an image telling indicator. Researchers found that the ability of children in telling the picture has not grown in line with expectations is 15 children there are only 3 children who can tell the appropriate language, 5 children who dare to appear in front and 4 children with a loud enough voice. Seeing these conditions, researchers tried to improve it by using media rotasia. The research was conducted at TK Pamekar Budi Desa Candisari Mranggen District for 3 months from August to October 2016 and using 2 cycles. The aspects studied in this improvement activity is the courage of children telling stories in front of the class, the suitability of the story with the picture and the volume of the child's voice when telling a story. Cycle I, researchers make improvements with the media rotation to tell stories with the title "Share it Fun" and "Queuing". During the learning obtained the findings that children are still a little difficult to operate media rotasia. In Cycle I, there is an increase in the students' learning spirit. The ability of students also increased rapidly. In the aspect of courage, there was an increase to 9 children (60%), story aspect 8 children (53%) and sound aspect to 6 children (40%). Looking at the results obtained in Cycle I and it has not reached the established success indicator that is as much as 80% then the researchers proceed to the improvement of learning Cycle II. In Cycle II this is obtained a satisfactory result. Children are accustomed to using media rotasia. Children are also more excited, this is seen during the learning process takes place, children are eager to appear in front and tell stories. The increase that occurred in Cycle II was as follows in the aspect of courage increased to 15 children (100%), story aspect 14 children (93%) and sound aspect to 14 children (93%). Looking at the results obtained in Cycle II and it has reached the established success indicator that is as much as 80% then the follower researchers proceed to the next cycle.